Burden and typing of rotavirus group A in Latin America and the Caribbean: systematic review and meta-analysis - Linhares, Alexandre C (2011)
Fil: Linhares, Alexandre C. Instituto Evandro Chagas. Secretaria de Vigilancia em Saúde. Virology Section; Brasil.